Sports Psychiatry Interventions Reduce the Incidence of Mental Health Crises Among Professional Athletes : A Systematic Review - Habibulloh , Firdaus Noval; Mahya , Faradilla Ainun; Halizah , Handini Nur; Awalludin, Muchammad Rizky; Zahra, Hilya Kamila; Aulia, Isma Alfina; Wasalwa, Manna; Adani , Muhammad Nathan; Azzahra , Naila Ausshafa; Khumairah, Nessya; Sheikh Abdullah, Siti Rozaimah (Tarqabin Nusantara Group, 2024)
Mental health crises among professional athletes have garnered increasing attention due to their impact on performance, career longevity, and well-being. This study evaluates the effectiveness of sports psychiatry interventions in reducing such crises. Using a mixed-methods approach, the research combines quantitative analysis of mental health outcomes with qualitative interviews of athletes across various disciplines over two years. Key interventions included cognitive-behavioral therapy, mindfulness training, and psychoeducation tailored to the demands of professional sports. The findings revealed a 40% decrease in reported mental health crises among athletes who participated in these programs. Qualitative data highlighted improved coping mechanisms, emotional regulation, and mental resilience, with athletes reporting greater psychological safety and confidence. These results demonstrate the critical role of sports psychiatry in fostering mental well-being and underscore the need for its integration into professional athletic programs to support sustainable mental health and performance.